The Use of Mendeley Reference in Improving the Quality of Scientific Writing and Compilation of Research Development for PGMI STAI Sangatta Kutai Timur Students - Ade Tuti Rossa Rochayati; Deti Rostini; Anjani Putri Belawati Pandiangan; Norsyam Amaly; Bidin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Mendeley is a very useful reference manager and research manager software for students. The use of Mendeley is very important in writing scientific papers and developing research and minimizing plagiarism. This study discusses the use of Mendeley references in improving the quality of student scientific writing and research development in the PGMI STAI Sangatta Madrasah Ibtidaiyah Teacher Education study program. This study aims to find out how to use Mendeley reference. This research method uses a qualitative research approach which aims to describe where data collection techniques are carried out, namely in-depth interviews with informants. The subjects of this study were students and heads of the Madrasah Ibtidaiyah Teacher Education Study Program PGMI STAI Sangatta East Kutai who were active in writing using Mendeley references to facilitate scientific writing assignments and research development.